Knowledge, perception, and clinical experiences on molar incisor hypomineralization amongst Portuguese dentists - Rita Maria Delgado; João Botelho; Vanessa Machado; José João Mendes; Luísa Bandeira Lopes (BMC, 2022)
Abstract Aim Molar incisor hypomineralization (MIH) is a prevalent oral health condition whose knowledge by dentists is key to the best clinical outcome. This study aimed to evaluate the knowledge, perceptions and clinical experiences of MIH among Portuguese dentists. Methods A cross-sectional structured questionnaire was distributed nationally through a web-based survey platform. Data concerning demographic variables, years of experience, dental specialty, MIH prevalence, diagnosis, severity, training demands and clinical management of MIH were collected. We calculated a knowledge score (KS), and compared data between Pediatric Dentists (PDs), General Dental Practitioners (GDPs) and other dental specialties (ODS). Results Overall, 2.2% of Portuguese dentists (n = 257) answered the questionnaire. Most participants reported having identified MIH in their practice (82.5%), with PD reporting the prevalence appeared to have increased, and practically all (91.7%) considered it a public health problem. Resin composite was often the used material to restore MIH teeth (56.0%), however PDs indicated glass ionomer cements as the preferred and preformed crowns a better option. The average KS on MIH was 41.3 (± 5.7), with GDPs having a similar score than PDs. Most respondents (94.9%) reported a lack of information about MIH and were willing to receive appropriate clinical training. Conclusions The average knowledge on MIH was considered low among Portuguese dentists. Respondents perceived an increased incidence of MIH, despite the lack of prevalence data in Portugal. The material of choice was Glass Ionomer and performed crowns, by PDs, while GDPs and ODS reported poor confidence to manage MIH. These results may serve future programs to increase knowledge, perceptions and clinical experiences towards MIH.